Low-threshold surface-emitting colloidal quantum-dot circular Bragg laser array - Yangzhi Tan; Yitong Huang; Dan Wu; Yunjun Wang; Xiao Wei Sun; Hoi Wai Choi; Kai Wang (Light: Science & Applications)
Abstract Colloidal quantum dots (CQDs) are attractive gain media due to their wavelength-tunability and low optical gain threshold. Consequently, CQD lasers, especially the surface-emitting ones, are promising candidates for display, sensing and communication. However, it remains challenging to achieve a low-threshold surface-emitting CQD laser array with high stability and integration density. For this purpose, it is necessary to combine the improvement of CQD material and laser cavity. Here, we have developed high-quality CQD material with core/interlayer/graded shell structure to achieve a low gain threshold and high stability. Subsequently, surface-emitting lasers based on CQD-integrated circular Bragg resonator (CBR) have been achieved, wherein the near-unity mode confinement factor (Γ of 89%) and high Purcell factor of 22.7 attributed to the strong field confinement of CBR enable a low lasing threshold of 17 μJ cm− 2, which is 70% lower than that (56 μJ cm− 2) of CQD vertical-cavity surface-emitting laser. Benefiting from the high quality of CQD material and laser cavity, the CQD CBR laser is capable of continuous stable operation for 1000 hours (corresponding to 3.63 × 108 pulses) at room temperature. This performance is the best among solution-processed lasers composed of nanocrystals. Moreover, the miniaturized mode volume in CBR allows the integration of CQD lasers with an unprecedentedly high density above 2100 pixels per inch. Overall, the proposed low-threshold, stable and compactly integrated CQD CBR laser array would advance the development of CQD laser for practical applications.